Managing the Built Environment for Health Promotion and Disease Prevention With Maharishi Vastu Architecture: A Review - Jon Lipman AIA; Lee Fergusson PhD; Anna Bonshek PhD; Robert H. Schneider MD, FACC (SAGE Publishing, 2022)
Background and objectives The evolution of healthcare from 18th-century reductionism to 21st-century postgenomic holism has been described in terms of systems medicine, and the impact of the built environment on human health is the focus of investigation and development, leading to the new specialty of evidence-based, therapeutic architecture. The traditional system of Vāstu architecture-a design paradigm for buildings which is proposed to promote mental and physical health-has been applied and studied in the West in the last 20 years, and features elements absent from other approaches. This review critically evaluates the theory and research of a well-developed, standardized form of Vāstu-Maharishi Vastu® architecture (MVA). MVA's principles include development of the architect's consciousness, universal recommendations for building orientation, siting, and dimensions; placement of key functions; and occupants' head direction when sleeping or performing tasks. The effects of isolated Vāstu elements included in MVA are presented. However, the full value of MVA, documented as a systematic, globally applicable practice, is in the effect of its complete package, and thus this review of MVA includes evaluating the experience of living and working in MVA buildings. Methods The published medical and health-related literature was systematically surveyed for research on factors related to isolated principles applied in MVA as well as on the complete system. Results Published research suggests that incorporating MVA principles into buildings correlates with significant improvements in occupants' physical and mental health and quality of life: better sleep, greater happiness of children, and the experience of heightened sense of security and reduced stress. The frequency of burglaries, a social determinant of health, also correlates. Potential neurophysiological mechanisms are described. Conclusions Findings suggest that MVA offers an actionable approach for managing a key social determinant of health by using architectural design as preventive medicine and in public health.